2020
DOI: 10.21203/rs.3.rs-54074/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence on Article 5.3 of FCTC (Tobacco Industry Interference in Tobacco Control Activities) in India - A Qualitative Scoping Study

Abstract: Background: Tobacco Industry (TI) strives to portray itself as being “socially responsible” and contest for pertinent decision-making positions, which it uses to deter, delay or dilute tobacco control measures. There is little documented evidence of Tobacco Industry Interference (TII) from India, the scope of their interference and challenges faced by the experts for effective tobacco control.Methods: A cross-sectional qualitative research design, based upon in-depth interviews (N=26), was used to explore the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Despite being opposed vehemently, In June 2016, the first phase of the Chilean Food Labelling and Advertising Law and initial assessments reported the benefits of such legislation [ 55 ]. This case study highlights that implementing effective food labels may not be easy and will face strong resistance from the industrialist due to deep-rooted industry interference similar to what has been documented for the tobacco [ 56 ]. Hence, a large-scale advocacy drive is required in this regard involving different levels of stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being opposed vehemently, In June 2016, the first phase of the Chilean Food Labelling and Advertising Law and initial assessments reported the benefits of such legislation [ 55 ]. This case study highlights that implementing effective food labels may not be easy and will face strong resistance from the industrialist due to deep-rooted industry interference similar to what has been documented for the tobacco [ 56 ]. Hence, a large-scale advocacy drive is required in this regard involving different levels of stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that the focus be shifted to supply reduction measures for tobacco elimination, indicating mass appeal and acceptability. 20, 21, 22…”
Section: Easier Said Than Donementioning
confidence: 99%
“…They recommended that the focus be shifted to supply reduction measures for tobacco elimination, indicating mass appeal and acceptability. 20,21,22 Considering the feasibility of a generational fade-out plan, one is faced with multiple sociocultural challenges. Epidemiological studies have reported the practice of smoking beedi (indigenous, hand-rolled cigarette, tobacco flakes rolled in a leaf ) in a large majority of South East Asian smokers, a market that continues largely unregulated in India.…”
Section: Easier Said Than Donementioning
confidence: 99%
“…More than 70% of tobacco consumers reported that advertisements by tobacco companies inspired their tobacco brand and product preferences, while >80% agreed that advertisements can alter consumer perceptions about the product advertised. 8, 22…”
Section: The Cat and Mouse Gamementioning
confidence: 99%
“…8,22 Timeline of Tobacco Advertisements and Control Measures in the South East Asia Region. Report of the Advisory Committee to the Surgeon General of the United States published in 1964.…”
mentioning
confidence: 99%